2022
DOI: 10.1140/epjds/s13688-022-00330-0
|View full text |Cite|
|
Sign up to set email alerts
|

Brexit and bots: characterizing the behaviour of automated accounts on Twitter during the UK election

Abstract: Online Social Networks (OSNs) offer new means for political communications that have quickly begun to play crucial roles in political campaigns, due to their pervasiveness and communication speed. However, the OSN environment is quite slippery and hides potential risks: many studies presented evidence about the presence of d/misinformation campaigns and malicious activities by genuine or automated users, putting at severe risk the efficiency of online and offline political campaigns. This phenomenon is particu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 54 publications
0
12
0
2
Order By: Relevance
“…As highlighted in other works 21 , 26 , 29 , 30 , 32 34 , the presence of well-defined discursive communities is the signal that users on Online Social Networks (OSNs) are strongly polarized, i.e., they tend to tend to split into groups, which one with same opinions and political orientation.…”
Section: Resultsmentioning
confidence: 94%
See 2 more Smart Citations
“…As highlighted in other works 21 , 26 , 29 , 30 , 32 34 , the presence of well-defined discursive communities is the signal that users on Online Social Networks (OSNs) are strongly polarized, i.e., they tend to tend to split into groups, which one with same opinions and political orientation.…”
Section: Resultsmentioning
confidence: 94%
“…We identified the discursive communities in the retweet networks and we investigated the presence of bow-tie structures in such communities. In previous works, discursive communities were shown to mirror the political orientation of users 21 24 , 26 , 29 , 30 , 32 34 , thus the analysis of their structure is of utmost importance to infer the way opinions create and circulate.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Second, we do not distinguish between the nature of the Twitter users, so we did not analyze the different effects that validated accounts, non-human accounts, and bots may bring into the conversation. Previous large-scale studies of Twitter data have demonstrated the influence bots can have on the exposure of human accounts to emotional content [5], and how they can coordinate and distort the discussion in controversial conversations [13,8]. Thus, we could incorporate botdetection methods and create a taxonomy of users to analyze their effects.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, entropy-based null models were presented in the literature of Complex Networks (Cimini et al, 2019): they represent a tailored and, at the same time, unbiased tool for detecting the statistically significant signal in complex networks. In the case of social networks, they were implemented in order to uncover coordinated behaviours of social bots (Caldarelli et al, 2020;Bruno et al, 2022), different semantic networks (Radicioni et al, 2021a,b;Mattei et al, 2021), accounts displaying the same information diets (Guarino et al, 2021) and the formation of discursive communities and their structures (Becatti et al, 2019;Caldarelli et al, 2021;Mattei et al, 2022;De Clerck et al, 2022a,b;Pratelli et al, 2023). In Ref.…”
Section: Introductionmentioning
confidence: 99%